TECHNOLOGICAL CYBERCRIME IN INDIA AND ITS HINDRANCE - Suriakala, M; Narayanasamy, P (International Journal of Computer Sciences and Engineering, 2025)
Today new technologies are entering into the world that is providing many informational resources. Technologies are needed in fast moving of information. Maximum security is created, but some lacks in security. It could be identified by cyber criminals and they are moving faster in global era and moreover they could be entering into human privacy. Information is wealth that could bring more facilities to business, entertainment, education and mobility. In India many cyber criminals are rapidly growing and breaking the security to earn money. This could be cultivated day to day by police, but many lacking in software’s and investigation. Every day cyber criminals are born and it could be endless one. This paper deals with many security depends on analyzing the various types are crime and deals with methodology like classification techniques to prevent the information from cyber-attacks